A novel crypto technique based ciphertext shifting - Farah R. Shareef (Egyptian Informatics Journal, 2020)
One of the significant issues in information security areas is a hidden exchange of data. There are several techniques for this purpose such as cryptography, steganography, etc. Generally, in cryptography, the secret message content is scrambled. In another hand in steganography, the secret message is embedded inside the cover medium. In this paper, a new crypto technique-based ciphertext shifting algorithm has been designed to improve the security for our previous work that combining cryptographic and steganographic. The improvement in the security of the secret message is done by changing the ciphertext value. The proposed shifting algorithm is used to rearranges the location of each character of ciphertext based on key value, in which the final ciphertext length is equivalent to encryption value but it different in value. The key strength of this method is two side one is trick the attacker from notice any change in ciphertext which is the same length as the original, so when used the common cryptanalysis will not get anything due to the original ciphertext has been changed. The second key strength of this method is that the shifting value is variable and dependent on key length. This method is inspected to be a very strong technique that can prevent common cryptography attacks such as a dictionary or brute-force attacks, etc.